Training of Gluten and Casein Free Snack Processing for Mothers of Children with Autism Spectrum Disorder - Tarigan, Novriani; Siahaan, Ginta; Lestrina, Dini (Talenta Publisher Universitas Sumatera Utara, 2020)
The gluten and casein-free (GCF) diet is one alternative ways in handling children with autism spectrum disorders (ASD). The aim of this community service activities was to improve the attitudes, motivations and skills of the mothers in order to be able to prepare GCF diet that are safe for consumption by ASD children. The target participants of this community service activity were 25 mothers of ASD children from the Pondok Peduli Autis Foundation in Medan. Stages of implementation consisted of socializing the activities, pre-test, and counseling on a GFC diet, training and demonstrations on processing of GCF snacks, as well as evaluating activities in the form of a post-test. The GCF products made in the training activities were purple sweet potato pudding, pumpkin pudding, hunkwe pudding, corn bakwan, cassava omelette, cassava pastel, and cassava croquette with vegetables. The average pre-test results on the participants' knowledge about GCF diets was 45.6. After counseling twice by using a